2022
DOI: 10.3390/biom12121870
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of N6-Carboxymethyllysine (CML), N6-Carboxyethyllysine (CEL), and Soluble Receptor for Advanced Glycation End-Products (sRAGE) Are Increased in Psoriatic Patients

Abstract: Psoriasis is a chronic, recurrent, and often severe skin disease which is frequently associated with metabolic disorders and increased risk of cardiovascular complications. One of the postulated links is an intensified process of advanced protein glycation and/or glycoxidation. Therefore, the aim of the study was to assess concentrations of N6-carboxymethyllysine (CML), N6-carboxyethyllysine (CEL), and soluble form of receptor for advanced glycation end-products (sRAGE) in psoriasis patients at different phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(61 reference statements)
1
0
0
Order By: Relevance
“…To what extent this effect may also have a favorable impact on metabolic comorbidities needs further investigation. Our findings are consistent with previous studies that have shown a reduction in SA in patients with psoriasis or PsA treated with adalimumab [ 39 ], or in patients with inactive disease [ 40 ]. Damasiewicz-Bodzek A et al showed that blood concentration of AGEs is higher during the active disease phase and decreases during remission [ 40 ].…”
Section: Ages and Psoriasissupporting
confidence: 93%
“…To what extent this effect may also have a favorable impact on metabolic comorbidities needs further investigation. Our findings are consistent with previous studies that have shown a reduction in SA in patients with psoriasis or PsA treated with adalimumab [ 39 ], or in patients with inactive disease [ 40 ]. Damasiewicz-Bodzek A et al showed that blood concentration of AGEs is higher during the active disease phase and decreases during remission [ 40 ].…”
Section: Ages and Psoriasissupporting
confidence: 93%